Examing the REITs Discount and Income Distribution in Malaysia - Yee, Wei Liang (2016)
This study investigated the REITs discount and income distribution in Malaysia over the 2005 to 2014 period. Malaysia REITs were trading at the range of 0.5453 to 1.5509 Price to Book ratio which some REITs are having heavy discount. Literatures show that Malaysia REITs received inadequate response from both local and foreign investors and underperform. Heavy discount has made property owners reluctant to list via REIT. The Panel Data Linear Regression Analysis was employed to examine the determinants against the dependant variables Price to Book and Distribution yield of Malaysia REITs. The results indicate that enhancement helps to improve REITs value most significantly. Gearing, size of REIT and Earning per unit (EPU) have significant relationship with both dependant variables. Total assets size of REITs improved the Price to Book ratio of REIT but affect the distribution yield slightly. Moreover, gearing improves the distribution yield but affect the REITs’ share price performance. Earning per unit helps to improve the distribution yield but distress the Price to Book. These finding suggest that enhancement initiatives is important for REIT managers to improve REITs value and share price. In conclusion, REIT size, gearing ratio and earning per unit is essential for REIT manager to manage and important to investors to make investment decision. Possible policy implications like Income Distribution Reinvestment plan should be implemented to help REITs to retain cash on hand. REIT manager role is important to deliver their specialist knowledge to manage the property and grow the REIT portfolio in size. Regulator and government play an important role to encourage REITs listing and governors.